The two-component system ArlRS is essential for wall teichoic acid glycoswitching in Staphylococcus aureus - Marieke M. Kuijk; Emma Tusveld; Esther Lehmann; Rob van Dalen; Iñigo Lasa; Hanne Ingmer; Yvonne Pannekoek; Nina M. van Sorge (mBio)
ABSTRACT Staphylococcus aureus is among the leading causes of hospital-acquired infections. Critical to S. aureus biology and pathogenesis are the cell wall-anchored glycopolymers wall teichoic acids (WTA). Approximately one-third of S. aureus isolates decorates WTA with a mixture of α1,4- and β1,4-N-acetylglucosamine (GlcNAc), which requires the dedicated glycosyltransferases TarM and TarS, respectively. Environmental conditions, such as high salt concentrations, affect the abundance and ratio of α1,4- and β1,4-GlcNAc WTA decorations, thereby impacting biological properties such as antibody binding and phage infection. To identify regulatory mechanisms underlying WTA glycoswitching, we screened 1,920 S. aureus mutants (Nebraska Transposon Mutant Library) by immunoblotting for differential expression of WTA-linked α1,4- or β1,4-GlcNAc using specific monoclonal antibody Fab fragments. Three two-component systems (TCS), GraRS, ArlRS, and AgrCA, were among the 230 potential hits. Using isogenic TCS mutants, we demonstrated that ArlRS is essential for WTA β1,4-GlcNAc decoration. ArlRS repressed tarM expression through the transcriptional regulator MgrA. In bacteria lacking arlRS, the increased expression of tarM correlated with the absence of WTA β1,4-GlcNAc, likely by outcompeting TarS enzymatic activity. ArlRS was responsive to Mg2+, but not Na+, revealing its role in the previously reported salt-induced WTA glycoswitch from α1,4-GlcNAc to β1,4-GlcNAc. Importantly, ArlRS-mediated regulation of WTA glycosylation affected S. aureus interaction with the innate receptor langerin and lysis by β1,4-GlcNAc-dependent phages. Since WTA represents a promising target for future immune-based treatments and vaccines, our findings provide important insight to align strategies targeting S. aureus WTA glycosylation patterns during infection.IMPORTANCEStaphylococcus aureus is a common colonizer but can also cause severe infections in humans. The development of antibiotic resistance complicates the treatment of S. aureus infections, increasing the need for antibiotic alternatives such as vaccines and therapies with bacterial viruses also known as phages. Wall teichoic acids (WTA) are abundant glycosylated structures of the S. aureus cell wall that have gained attention as a promising target for new treatments. Importantly, WTA glycosylation patterns show variation depending on environmental conditions, thereby impacting phage binding and interaction with host factors, such as antibodies and innate pattern-recognition receptors. Here, we show that the two-component system ArlRS is involved in the regulation of WTA glycosylation by responding to environmental changes in Mg2+ concentration. These findings may support the design of new treatment strategies that target WTA glycosylation patterns of S. aureus during infection.